KAMPANYE DAN TELEVISI (Analisis Pemberitaan Kampanye Pemilu Legislatif 2009 di TV Borobudur) - Julianto, Edi Nurwahyu (Universitas Semarang, 2010)
In the context of the current information age, media power is great considered in the flow of information spread quickly and widely. The political elite use media to socialize the political agenda. Institutions of mass media like television and newspapers is believed to have ability in organizing the production, reproduction and distribution of knowledge significantly. A series of symbols that gives meaning of the reality of